The red badge of courage - Crane, Stephen 1871-1900.; Vogel, Malvina G.; Cruz, E. R. (Eufronio Reyes) 1934- (New York Baronet Books., 1993)
In the spring of 1863, while engaged in the fierce battle of Chancellorsville in Virginia, a young Union soldier matures to manhood and finds peace of mind as he comes to grips with his conflicting emotions about war.
Keywords: Chancellorsville, Battle of, Chancellorsville, Va., 1863 -- Juvenile fiction; Chancellorsville, Battle of, Chancellorsville, Va., 1863 -- Fiction; War -- Fiction; Coming of age -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction